Managerial accounting - Wild, John J. (McGraw-Hill. Irwin, 2007)
The author provides a balance of small and large business examples, integration of new computerized learning tools, superior end-of-chapter materials, and highly engaging pedagogical learning structures. Technology tools such as Homework Manager provide students with further advantages as they learn and apply key accounting concepts and methods